SUPPORTING SOCIALY EXCLUDED ROMANY (GYPSY) PARENTS IN PROVISION QUALITY PARENTING - Navratil, Pavel (European Scientific Journal, ESJ, 2013)
The very aim of the presented text is to formulate goals and themes for the methods of social work with socially excluded Roma families in the Czech Republic. My suggestions are based on the interviews which I conducted with 17 experts (social workers, Roma pedagogical assistants, Roma activists, teachers and clerics). I talked with them about the living conditions of socially excluded Roma families. While in my previous articles I addressed the analysis of the interviews and described how our conversation partners perceived the performance of parental functions, now I would like to address the implications of the research results for the practice of social work. The reason for the formulation of the principles and methods of social work in the Roma families is very important. Effective social work with the families could be prevention of child removal.